2020
DOI: 10.1097/iae.0000000000002411
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Lifetime Patterns in Macular Telangiectasia Type 2

Abstract: Purpose: Type 2 idiopathic macular telangiectasia (MacTel) is a rare bilateral neurodegenerative disease characterized by alterations in the macular capillary network leading to central vision loss. The purpose of this study was to quantify disease-specific retinal fluorescence lifetime patterns in patients with MacTel using fluorescence lifetime imaging ophthalmoscopy. Participants: Both eyes of 14 patients (mean age ± SEM, 67.8 ± 6.4 years) with a clinical diagnosis of MacTel Type 2 and 14 healthy age-matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…In MacTel, a different pattern can be found. 44 , 57 The FLIO pattern in MacTel appears in the SSC as a temporal area of prolonged FLIO lifetimes, which is typically not exceeding the MacTel area of approximately 5° vertical and 6° horizontal eccentricities. 13 Regarding choroideremia, we were able to confirm findings from a previous study indicating that its appearance in FLIO and autofluorescence intensity imaging are not necessarily concordant.…”
Section: Discussionmentioning
confidence: 99%
“…In MacTel, a different pattern can be found. 44 , 57 The FLIO pattern in MacTel appears in the SSC as a temporal area of prolonged FLIO lifetimes, which is typically not exceeding the MacTel area of approximately 5° vertical and 6° horizontal eccentricities. 13 Regarding choroideremia, we were able to confirm findings from a previous study indicating that its appearance in FLIO and autofluorescence intensity imaging are not necessarily concordant.…”
Section: Discussionmentioning
confidence: 99%
“…FLIO has shown promising results as a prototype; it holds the potential to diagnose retinal diseases at early stages and may be on its way to become an important imaging modality in the future. [3][4][5][6][7][8][9][10][11][12]25 To use FLIO in clinical studies, background knowledge regarding specific influences on FLIO is important. A previous study by Dysli et al 16 nicely demonstrated that FLIO has good test-retest reliability, which holds true for miosis and mydriasis.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 Various studies have shown that different retinal diseases, such as age-related macular degeneration and macular telangiectasia type 2 (MacTel), can be detected with FLIO even before other clinical signs of the disease appear, and well before damage is manifest. 5 9 Furthermore, FLIO is able to detect disease progression, which was especially highlighted in various cases of Stargardt disease, in which FLIO detects progression approximately 1 to 2 years before these changes are visible in conventional autofluorescence imaging. 10 , 11 In patients with early retinal toxicity due to drugs, such as hydroxychloroquine (Plaquenil), FLIO may also be helpful.…”
Section: Introductionmentioning
confidence: 99%
“…FLIO shows specific patterns of FLIO lifetimes in AMD, MacTel, hydroxychloro- quine toxicity, Stargardt disease, and other inherited retinal diseases, and it is capable of distinguishing one disease from another. [20][21][22][24][25][26][27]29,37,38,40,41 Changes in FLIO lifetimes can present before any structural, anatomical, or autofluorescence intensity changes appear in conventional imaging techniques. 20,23,24,42 For example, eyes of patients with AMD display a ring-shaped pattern of prolonged FLIO lifetimes in the macular area, which is not seen in FAF intensity images.…”
Section: Discussionmentioning
confidence: 99%
“…Early FLIO lifeetime changes have been detected in Stargardt disease, patients with macular telangiectasia type 2 (MacTel), and patients who may develop retinal toxicity due to hydroxychloroquine (Plaquenil) supplementation. [20][21][22][23][24] Recently, early retinal changes in family members of patients with MacTel were found with FLIO. 24 Several other diseases, such as age-related macular degeneration (AMD), diabetic retinopathy, and Alzheimer disease, similarly exhibit altered FLIO lifetimes in early disease stages.…”
Section: Introductionmentioning
confidence: 99%